Foster placements : why they succeed and why they fail - Sinclair, Ian, 1938- (Supporting parents., 2005)
How can we determine success in foster placements? Based on exhaustive research, the authors discuss the primary concerns in foster placement planning, considering the high frequency of placement breakdowns, their impact on the child's behaviour and school performance, and the challenges this places on foster families. The specific needs of the foster child are given close attention in determining a pathway to success. By monitoring and describing the individual characteristics of the child within the context of the placement, the authors are able to reveal what types of supports are most bene.